المـرأة و غوايـة الكتابـة - سعــاد, طويـل (Sciences humaines; Vol. 25 (2012): SCIENCES HUMAINES)
تروم هذه الدراسة، باتخاذها المحكي الروائي لأحلام مستغانمي مدار مقاربة، إلى مكاشفة صراع المرأة / الكاتبة/ الساردة،  مع الرجل / المؤسس لفعل الكتابة تاريخيا. صراع تعلنه المرأة من مبدأ الوعي بالكتابة، وهو وعي بالأنوثة المستلبة، سعيا منها للهيمنة على فعل الكتابة و ذلك بـ" تخليص اللغة من فحولتها التاريخية".   This study which takes Ahlem Moustaghnmi ‘s novel as practical space, aims  to show the conflict of the woman/ the writer / the narrator with the man; the founder of writing act historically. A conflict that woman begins from her consciousness of writing which is a consciousness of a stolen feminism. Her aim is to control the writing act by rescue the language from its historical male.